Food Adulteration and Its Impact on Health - Pantha, Rodana (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
Food adulteration is the addition or mixing of inferior, harmful, substandard, useless or unnecessary substances to foods. This loses the nutritional content and quality of food items. Adulteration poses a number of health hazards which include health diseases and weaken the immune system. The main objectives of this study was to aware of consumer about food adulteration and use of organic food items. Department of Food Technology and Quality Control under Ministry of Agricultural and Cooperatives is the major Government Institution responsible for food safety and quality management. There is a need of public campaign to make the general public aware about the quality of food items. We consumer should be aware of and conscious while buying food items. This study is based on the informations taken from secondary sources. At the end some suggestions and recommendations are given for improving the health status of consumers.